2013
DOI: 10.2188/jea.je20120121
|View full text |Cite
|
Sign up to set email alerts
|

Declining Rates of Tobacco Use in the Japanese Medical Profession, 1965^|^ndash;2009

Abstract: BackgroundAlthough there has been a downward trend in smoking rates among medical doctors in recent years, rates have been higher among Japanese doctors when compared internationally.MethodsWe extensively reviewed all published English- and Japanese-language articles that reported the smoking rates of Japanese doctors.ResultsA total of 36 articles were examined, most of which had been conducted as postal surveys, usually by a national, prefectural, or local medical association. Sample sizes ranged from 17 to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Thus, the prevalence of smoking among physicians in Estonia is still higher than in many developed countries. However, smoking prevalence among physicians in some developed countries like France, Italy and Japan has remained high with the prevalence of current smoking over 25% [ 18 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the prevalence of smoking among physicians in Estonia is still higher than in many developed countries. However, smoking prevalence among physicians in some developed countries like France, Italy and Japan has remained high with the prevalence of current smoking over 25% [ 18 , 41 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previous reports have shown that smoking prevalence among physicians in high income countries (e.g. the United Kingdom, the United States, Australia, and Finland) has decreased [ 15 – 18 ]. The prevalence of smoking among physicians was 4% in US in 1984 and 3% in Australia in 1996 already [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is well-known that smokers tend to have poorer health behaviors than their non-smoking counterparts [ 32 ] and obtaining vaccinations is not an exception to this rule [ 6 , 33 ]. In the current study we found a weak association between mistrust for governmental recommendations for vaccination in Japan and individual smoking status.…”
Section: Discussionmentioning
confidence: 99%
“…Tobacco use has been similarly declining among doctors in some other Asian regions. A recent examination of Japanese research, for example, elucidated a continuous decline of smoking among Japanese doctors since the mid 1960s [40]. Not all regions have demonstrated consistent, if any, declines in tobacco usage among doctors.…”
Section: Discussionmentioning
confidence: 99%